Seven-Grooved-Rod, Side-Pumping Concept for Highly Efficient TEM00-Mode Solar Laser Emission through Fresnel Lenses - Hugo Costa; Dawei Liang; Joana Almeida; Miguel Catela; Dário Garcia; Bruno D. Tibúrcio; Cláudia R. Vistas (Photonics, 2023)
Low-cost, lightweight, and easily available Fresnel lenses are a more alluring choice for solar laser power production, when compared to the costly and complex heliostat-parabolic mirror systems. Therefore, a seven-rod solar laser head was designed and numerically studied to enhance the efficiency in TEM00-mode laser power production, employing six Fresnel lenses with 10 m2 total collection area for collection and concentration of sunlight. Six folding mirrors redirected the solar rays towards the laser head, composed of six fused silica aspheric lenses and rectangular compound parabolic concentrators paired together for further concentration, and a cylindrical cavity, in which seven Nd:YAG rods were mounted and side-pumped. With conventional rods, total TEM00-mode laser power reached 139.89 W, which is equivalent to 13.99 W/m2 collection efficiency and 1.47% solar-to-TEM00-mode laser power conversion efficiency. More importantly, by implementing rods with grooved sidewalls, the total laser power was increased to 153.29 W, corresponding to 15.33 W/m2 collection and 1.61% conversion efficiencies. The side-pumping configuration and the good thermal performance may ensure that the seven-grooved-rod system has better scalability than other previously proposed schemes.